Protecting democracy from abroad: democracy aid against attempts to circumvent presidential term limits. Issue 1 (2nd January 2022) - Nowack, Daniel; Leininger, Julia
ABSTRACT: The article addresses the question of whether international democracy aid helps to protect presidential term limits – a commonly accepted but increasingly challenged safeguard for democracy. According to our analysis, democracy aid is effective in countering attempts to circumvent term limits, thus, it contributed towards protecting democratic standards in African and Latin American countries between 1990 and 2014. Democracy aid helps to fend off term-limit circumventions, but it is not as effective in deterring presidents from trying to circumvent presidential term limits. Our analysis furthermore suggests that there is double the risk of an attempt to circumvent term limits in Latin American than in African states. Although our results confirm prior findings that "targeted aid" such as democracy aid makes a difference for maintaining democratic institutions, it challenges studies that argue democracy assistance has become "tame." Our findings furthermore support previous indications that more refined theories on the effects of democracy aid in different phases of domestic processes are necessary, in particular in the face of global autocratization trends.